Preparing Adaptive Graduates, Islamic and Professional in the Era Society 5.0 - Effendi, Fauzan; Fahyuni, Eni Fariyatul (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract. The evolution of Society 5.0, characterized by advancements in Artificial Intelligence (AI) and the Internet of Things (IoT), necessitates that Islamic higher education institutions adapt to these changes. General Background: The Faculty of Islamic Studies at Universitas Muhammadiyah Sidoarjo (UMSIDA) aims to produce graduates who possess both Islamic values and professional competencies, particularly in AI. Knowledge Gap: However, there is a lack of curricula that effectively integrate AI with ethical considerations rooted in Islamic teachings. Aims: This paper proposes a development plan to enhance curricula, faculty competencies, and the responsible integration of AI. Results: The findings emphasize the need for graduates to collaborate effectively with AI while maintaining ethical standards. Novelty: This study introduces a strategic vision for 2032, focusing on innovative curriculum design and faculty development in line with Islamic principles. Implications: By equipping graduates with the necessary skills and ethical awareness, this framework ensures the relevance of Islamic education in a technologically advanced society, preparing them for future challenges with integrity and competence. Highlights: Curriculum Integration: Emphasizes the need for curricula that blend AI skills with Islamic ethical teachings. Graduate Competence: Aims to prepare graduates for collaboration with AI technologies while upholding professional integrity. Strategic Vision: Proposes a framework for 2032 focused on innovation and adaptability in Islamic higher education. Keywords: Profesional, Islamic Value, Adaptation, Era Society 5.0, Artificial Intelligence, Curriculum Development